การพัฒนาเครื่องอบแห้งพลังงานชีวมวลโดยมีพลังงานแสงอาทิตย์ช่วยสาหรับเกษตรกรในชุมชนที่ไฟฟ้าสาธารณะเข้าไม่ถึง - วรรณรัตน์ ฉั่วตระกูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purposes of this research were to design and construct a biomass dryer assisted with solar energy and to study the performance of the dryer. This dryer is designed for farmers, especially farmers in off-grid communities. The dryer consists of a drying chamber was 1.5x2x1.5 m3, a boiler set and solar cell panels. A compressed sponge is used as a drying product to test the distribution of air temperature and moisture uniformity inside the drying chamber. The initial moisture content was about 320%db. A compressed sponge was dried until the moisture content was less than 10%db. There are three different thermal energy modes, which are solar energy mode, biomass energy mode and biomass assisted with solar energy mode. From the experiments, it was found that using biomass assisted with solar energy mode has the best performance, due to the average temperature difference between the top tray and the bottom tray was less than 3oC and the average of temperature varies from 50oC to 61oC. The moisture content in all trays was uniform and dried at nearly the same time, and dried within 3.25 h. The average specific drying rate was 0.98 kgwater/kgdry product/h, the specific energy consumption was 60.73 MJ/kgwater and the overall thermal efficiency was 4.12%. Additionally, this dryer can reduce the contamination of products from combustion smoke and ash, and can be auxiliary heat sources during periods of insufficient solar radiation or nighttime.